Public Health Services in Local Government Analysis of Quality and Accessibility of Health Services for the Community - Muliati Muliati; Indra Kristian; Erwan Prastiawan; Reza Yuridian Purwoko; Jovita Aurelia (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Health services in local governments are a crucial element in meeting public health needs. This research aims to explore the factors that influence the quality and accessibility of health services at the local level, with a focus on health infrastructure, human resources, financing, health technology, and community participation. This research aims to analyze the quality and accessibility of public health services in local government. This research uses a descriptive qualitative approach by collecting data from previous studies that are relevant to health service issues in local government. The data that has been collected will be processed to support a more in-depth analysis of these issues. The results of this study found that the evaluation of health infrastructure, availability of human resources, financing, and health policies play an important role in the quality and accessibility of health services in local governments. While the adoption of technology in healthcare offers great opportunities to improve efficiency and effectiveness, privacy and technology access challenges still need to be addressed. Community participation and health awareness encourage healthy behavior and play an active role in health maintenance, which in turn can support the quality of health services. This research provides a holistic and in-depth view of the health system in local government, illustrating the need for collaboration between government, health service providers, and communities in dealing with complex health issues.